2012
DOI: 10.1177/0883911512447211
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of nanohydroxyapatite on electrospun poly(l-lactic acid)/gelatin by an alternate soaking process: A biomimetic scaffold for bone regeneration

Abstract: Biomimetic nanocomposite scaffolds were fabricated by electrospinning poly(l-lactic acid) and a blend of poly(L-lactic acid)/gelatin to eliminate the use of collagen. The scaffolds were mineralized via alternate soaking in calcium and phosphate solutions, whereby 66.8% nanohydroxyapatite formation was successfully induced which is similar to that of native human bone (60%). The poly(L-lactic acid)/gelatin scaffolds had uniform nanohydroxyapatite formation throughout the scaffold. The mineralization enhanced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…Other similar studies performed by Samiei et al and Feng et al also showed less proliferation on the scaffold containing HA. They demonstrated the reason of this to the number of cells that differentiation path had been activated for them . Seyedjafari et al also got the same results about PLLA nanofibrous scaffold coated with HA compared with PLLA only scaffold.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Other similar studies performed by Samiei et al and Feng et al also showed less proliferation on the scaffold containing HA. They demonstrated the reason of this to the number of cells that differentiation path had been activated for them . Seyedjafari et al also got the same results about PLLA nanofibrous scaffold coated with HA compared with PLLA only scaffold.…”
Section: Discussionsupporting
confidence: 61%
“…They demonstrated the reason of this to the number of cells that differentiation path had been activated for them. 45,46 Seyedjafari et al 6 also got the same results about PLLA nanofibrous scaffold coated with HA compared with PLLA only scaffold. Consequently, it can be concluded that the reason of decrease in cell proliferation on SH scaffold was activation of hydroxyapatite differentiation signal.…”
Section: Discussionmentioning
confidence: 64%
“…The scaffolds were mineralized via alternate soaking in calcium and phosphate solutions leading to formation on homogeneous hydroxyapatite nanoparticles. The mineralization process remarkably improved the tensile modulus and the tensile strength whilst the brittleness was not increased [11]. Rakmae et al used bovine bone-based hydroxyapatite (b-HA) as bioactive filler in a poly(lactic acid)-PLA matrix.…”
Section: -Introductionmentioning
confidence: 99%
“…Electrospun synthetic or biopolymer-based fibers typically have a low (~MPa) tensile modulus and strength [4547]. In contrast, all nHAp-containing fibers here have a tensile strength and modulus similar or higher than those of other electrospun polymer-nHAp composite fiber mats reported in the literature [28, 46, 48].…”
Section: Resultsmentioning
confidence: 98%